Emergency Remote Education: Apps and educational platforms used during the pandemic - Ruiz Mendoza, Karla Karina (2022)
The objective of this work was to analyze the use and management of educational applications and platforms by teachers through an online survey to understand the scope and limitations within the so-called Emergency Remote Education due to the Covid pandemic- 19. The research is a descriptive, cross-sectional observational study. The survey was applied in January 2021, through Google forms, which collected information on 91 teachers in the state of Baja California, with ages ranging from 22 to 58 years old. The results indicate that teachers are using the tools with which they have been approached.